Impacto socioeconómico de la Pythiosis (Espundia equina) en la vereda Caño Chiquito del municipio de Paz de Ariporo Casanare (2023)
Introduction. The horse is the animal most used in the region of the Eastern Plains for the development of work in the field as the work of level for their skill, ability and intelligence, so that the care of their health is of great importance, that can be threatened by a pathology called Pythiosis or Espundia, caused by a fungus Pythium insidiosum, which affects the equines when winter comes from contact with contaminated water, leaving neoplasms in the abdomen extremities, chest, mouth, eyes and gastrointestinal, weakening the animal, in its immune system that can cause death. Objective: The research aimed to measure the socioeconomic impact of the presence of equine pythiosis in the herds of the Caño Chiquito village Paz de Ariporo municipality. Materials and methods: through a socioeconomic survey at the level of administrators and herd owners applied to 51% of the properties reported in the study area, which included case reports, deaths, affectations, ages, weather and treatments; as well as taking blood and biopsies in animals with lesions, for analysis blood count, blood chemistry and histopathological diagnosis respectively. Results: 92.3% of the respondents did not have knowledge about the causal agent of the disease due to the fungus, and they know the pathology as equine espundia or sore brava in 46.2% respectively, affecting young animals in 42% and 26.9% in adults; 14 horses were reported per herd that are affected with mortality in males of 28.6% and in females of 29.3%; used as treatment 65.3% Corticosteroids, 23.1% used them together with another drug and 15.4% empirical treatment without the use of drugs. The histopathological diagnosis confirms the presence of the fungus. Conclusions: The pitiosis in equine represents a great social, labor and economic impact that affects the productive development of the herds. © 2018 Veterinary Organization. All rights reserved.